2008
DOI: 10.1016/j.ejca.2008.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Do phytoestrogens reduce the risk of breast cancer and breast cancer recurrence? What clinicians need to know

Abstract: . Do phytoestrogens reduce the risk of breast cancer and breast cancer recurrence? What clinicians need to know. European journal of cancer (Oxford, England : 1990), 44(13), 1799 -1806 . DOI: 10.1016 /j.ejca.2008 Published in: European journal of cancer (Oxford, England : 1990) Queen's University Belfast -Research Portal: Link to publication record in Queen's University Belfast Research Portal General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…The biological complexity of phytoestrogens is well described [5]. Understanding the in vivo effects of phytoestrogens is complicated by different forms and quantities of intake and individual metabolic differences.…”
Section: Introductionmentioning
confidence: 99%
“…The biological complexity of phytoestrogens is well described [5]. Understanding the in vivo effects of phytoestrogens is complicated by different forms and quantities of intake and individual metabolic differences.…”
Section: Introductionmentioning
confidence: 99%
“…This finding highlights the need to educate patients about the harmful effects of such products, providing guidance for supplements to avoid. As patients may not readily disclose information about supplement consumption to their clinician [43] and their habits may change periodically, it may be advisable for clinicians to regularly ask patients about their supplement use and suggest caution due to a lack of evidence of any beneficial effects [44]. At the same time, more research on the effects of oestrogenic and other supplements in breast cancer patients and tighter regulations on labelling are needed.…”
Section: Supplement Use Before and After Diagnosismentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Two recently published metaanalyses (including our own) showed that high serum or urinary enterolactone levels were associated with a nonsignificant reduced postmenopausal breast cancer risk, whereas high consumption of dietary lignans was associated with a significant reduced postmenopausal breast cancer risk. 22,23 The objective of our study was to examine the association of the major serum enterolignan (enterolactone) with the risk of postmenopausal breast cancer in a large German study population with Western dietary habits. Additionally, we investigated whether this association differs by ER, progesterone receptor (PR) or herceptin receptor (HER2) status of the tumor.…”
mentioning
confidence: 99%